Improvisation, Creativity, and Consciousness : Jazz as Integral Template for Music, Education, and Society - Sarath, Ed (Book collections on Project MUSE., 2013)
Using insights from Integral Theory, this book describes how the improvisational methods of jazz can inform education and other fields.